2005
DOI: 10.1007/s10585-005-7889-x
|View full text |Cite
|
Sign up to set email alerts
|

Human and Rat Glioma Growth, Invasion, and Vascularization in a Novel Chick Embryo Brain Tumor Model

Abstract: The mechanisms that control the insidiously invasive nature of malignant gliomas are poorly understood, and their study would be facilitated by an in vivo model that is easy to manipulate and inexpensive. The developing chick embryo brain was assessed as a new xenograft model for the production, growth, and study of human and rat glioma cell lines. Three established glioma lines (U-87 MG, C6, and 9L) were injected into chick embryo brain ventricles on embryonic day (E) 5 and brains were examined after several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…4e) would be indicative of cell behavior. We also previously found that glioma cells transfected with DNA encoding an adhesion molecule exhibited a constant decreased migration velocity (Cretu et al 2005). Thus, our method of quantitation and analysis of cell migration rates over closely spaced time points allowed detection of dynamic changes in migration velocity, such as initial or subsequent increases or decreases, or of constant velocity.…”
Section: Cell Migration Dynamicsmentioning
confidence: 78%
See 1 more Smart Citation
“…4e) would be indicative of cell behavior. We also previously found that glioma cells transfected with DNA encoding an adhesion molecule exhibited a constant decreased migration velocity (Cretu et al 2005). Thus, our method of quantitation and analysis of cell migration rates over closely spaced time points allowed detection of dynamic changes in migration velocity, such as initial or subsequent increases or decreases, or of constant velocity.…”
Section: Cell Migration Dynamicsmentioning
confidence: 78%
“…One of our main focuses was to refine the commonly used scratch or wound healing assay into a highly quantitative Super Scratch assay. The scratch assay before this work had not progressed beyond a single or few timepoint assay where measurements were made of distance between edges (Maschler et al 2005;Zhu et al 2004;Pratt et al 2005;Wadham et al 2003;Besson et al 2004;Cretu et al 2005;Hoang et al 2004;John et al 2004;Ray et al 2003;Lynch et al 2005;Yarrow et al 2004), number of cells entering a defined area (Petridis et al 2004;Nishio et al 2005;Zhu et al 2004;Piccolo et al 2002;Robinet et al 2005;Raftopoulou et al 2004;Zhu et al 2005), or qualitative assessment without quantitation (Gavert et al 2005;Yoshida et al 2004;Zhang et al 2005;Herren et al 2001;Lee et al 2004;Motegi et al 2003;Laurent-Matha et al 2005;Miao et al 2005). We have shown that such a method of analysis is not as accurate a representation of cell migration as tracking individual cells starting from the advancing front of the wound.…”
Section: Discussionmentioning
confidence: 98%
“…The experimental settings of the coculture model presented here partially simulate the complex microenvironment in the periphery of a diffuse glioma, with a reduced number of tumor cells and with the majority of C6 cells migrating instead of undergoing proliferation. In addition to the widespread use of rodent brains, recent use of the chick brain to examine human and rat glioma growth, invasion, and vascularization in vivo (Cretu et al, 2005) has demonstrated that chicken nervous tissue is suitable for tumor-xenograft and C6-cell studies. The present work enhanced this approach by creating an in vitro environment similar to that of white-matter tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted injection of tumour cells in embryonic tissues can give rise to tumours on a relatively short time scale, as recently demonstrated by the appearance of vascularised tumours 11-14 days after introduction of established glioma cell lines into developing chick brain. (61) As previously mentioned, the chick embryo model offers a rare access to the embryonic environment, which is known to exert a critical effect on the regulation of tumour cells. Early work on the mouse embryo has established that events taking place during embryonic development are able to control and reprogram cells otherwise known to be tumourigenic.…”
Section: Adult Stem Cell Researchmentioning
confidence: 99%